Analisis Penyaluran Dana Desa Berdasar Permenkeu 201 Tahun 2022 Terhadap Implementasi Penyaluran Dana Desa Di Kabupaten Probolinggo - Erlangga, Yogha; Haris, R Abdul; Amani, Tatik; Karnadi, Karnadi; Yoga, Yunaz Farada (Universitas Panca Marga, 2024)
This study aims to identify the factors influencing the delay in the distribution of Village Fund in Probolinggo Regency and propose solutions for accelerating the process. Using a qualitative approach, data were collected through interviews and in-depth analysis. The findings indicate three main factors contributing to the delay: the quality of human resources at the village level affecting the operation of the Village Financial Management System (Siskeudes), the lack of operators at the subdistrict level, and the limited number of technical staff at the Community and Village Empowerment Office (PMD). To address these issues, capacity building for village officials through technical training, strengthened supervision by subdistricts, and expedited budget regulation formulation by the PMD Office are needed. This research is expected to provide insights for policymakers to accelerate the distribution of Village Fund, supporting village economic development and community welfare.